Performance evaluation of Direct-Seeded Rice (DSR) conventional transplanted rice in Bihar - CHANDRA, SUBHASH; SINGH, N K; SINHA, J P; KUMAR, PANKAJ (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted during kharif 2018 at the experimental farm of Dr. Rajendra Prasad Central Agricultural University, Pusa and Bihar Agricultural University, Sabour with popular varieties of paddy to study growth, yield and economic assessment under three paddy production systems as treatments T1, T2 and T3 i.e Dry-DSR by rice-wheat seeder equipment, Dry-DSRB by broadcasting of seeds and TPR: manual transplanting of seedling in puddled soil, respectively. The cultivars, viz. Rajendra Bhagwati, Rajendra Saraswati and Rajendra Sweta, recorded maximum yield 5.59 t/ha, 5.16 t/ha and 4.16 t/ha in treatment T1, followed by treatment T3 (5.23 t/ha, 4.92 t/ha and 3.75 t/ha), respectively. The yield of Rajendra Bagwati and Rajendra Saraswati in treatment T2 was 4.75 t/ha and 4.86 t/ha, respectively. Benefit-cost ratio of Rajendra Bhagwati in treatments T1, T2 & T3 were found 4.38 : 1, 3.74 : 1 & 3.19 : 1, respectively followed by Rajendra Saraswati and Rajendra Sweta with values in ratios 3.97:1, 3.85:1 & 2.97:1 as well as 2.97:1, 2.84:1 and 1.99:1, respectively. Obviously, the Dry-DSR of by rice wheat seeder equipment has been found economical viable technology for growing rice in respect of yield and net benefit.